From Khartoum to Jerusalem: the Dragoman Solomon Negima and his clients (1885-1933) - Mairs, Rachel (Bloomsbury Publishing, 2016)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Dedication page -- Contents -- Acknowledgements -- Figures -- Timeline -- 1 Introduction -- The testimonial book -- Solomon Negima -- Finding Solomon -- Writing Oriental lives -- Tourism and pilgrimage -- 2 The Sudan, 1885 -- Shall We Annex Egypt? -- Comrades on the Nile -- Th e Desert Column -- Interpreters on the Nile: Muhammed Effendi Ibrahim -- Solomon's officers -- 3 Tourists and Pilgrims -- Mr Woolrych Perowne's Co-operative Educational Tours -- The recent pilgrimage to Jerusalem -- The 1895 party